New Insight on Vitality Differences for the Penaeid Shrimp, Fenneropenaeus chinensis, in Low Salinity Environment Through Transcriptomics - Liu, Jun; Zhang, Daizhen; Zhang, Lei; Wang, Zhengfei; Shen, Jie (Frontiers in Ecology and Evolution, 2022)
Excessive rainfall changes salinity in shrimp farming ponds in short period and exerts low salinity stress on the outdoor breeding shrimp under global warming. Fenneropenaeus chinensis can have different performance on vitality in low salinity environments. To reveal mechanisms of vitality difference in shrimp living in low saline environments. This study based on the normal and moribund F. chinensis in 10 ppt salinity environment using high-throughput sequencing identifies 1,429 differentially expressed genes (DEGs), 586 of which are upregulated, while 843 of which are downregulated in the normal group (FCN10) as compared to the moribund group (FCM10). Meanwhile, another transcriptomic analysis is conducted on the normal and moribund shrimp from 25 ppt (FCN25 vs. FCM25) salinity environment as the control, in which 1,311 DEGs (upregulated: 327 genes, downregulated: 984 genes) are identified. In this study, intersective pathways, GO (Gene Ontology) categories and DEGs from the two groups of comparative transcriptome are investigated. The two intersective pathways (Metabolism of xenobiotics by cytochrome P450, Pentose, and glucuronate interconversions) significantly enriched by DEGs are related to detoxification. In these two pathways, there is one vitality regulation-related gene (VRRG), the Dhdh (dihydrodiol dehydrogenase), which is upregulated in both the groups of FCN10 and FCN25 as compared to the groups of FCM10 and FCM25, respectively. Similarly, in the 25 top intersective GO categories, four VRRGs are revealed. Three of them are upregulated (Itgbl, kielin/chordin-like protein, Slc2a8, solute carrier family 2, facilitated glucose transporter member 8-like protein and Cyp3a30, cytochrome P450 3A30-like protein); one of them is downregulated (Slc6a9, sodium-dependent nutrient amino acid transporter 1-like protein isoform X2). These GO categories are related to transmembrane transporter activity of substance, enzyme inhibitor activity, monooxygenase activity. RT-qPCR analysis further verifies the VRRGs. The study gives new insight into understanding the vitality differences for F. chinensis, in low salinity environment. The pathways and DEGs in response to low salinity stress in modulating the vitality of F. chinensis that could serve as tools in future genetic studies and molecular breeding.